Using maturity method to predict compressive strength of acrylic polymer concrete containing TMPTMA or silane at sub-zero curing temperatures - 이한승 (COMPOSITES COMMUNICATIONS, 2023)
Acrylic polymer concrete (APC) is a fast-setting and high-strength material with low freezing point, and can gain strength even at sub-zero temperatures, making it an excellent option for repairing pavements and roads during cold weather. Accurately estimating the compressive strength of APC is critical for determining safety time to open the pavement to traffic. Unfortunately, traditional maturity methods, such as those recommended by ASTM C1074 for Portland cement concrete, cannot be applied directly for strength estimation of APC. In order to estimate the compressive strength of APC containing 0-5 phr trimethylolpropane trimethacrylate (TMPTMA) or 0-2 phr silane cured at sub-zero temperatures, the Arrhenius equation-based maturity method has been modified and utilized for the first time in this study. An exponential function is adopted to characterize strength development of APC cured at different temperatures (-20-0 degrees C), with the assumption that the ultimate compressive strength of APC is independent of curing temperature. The corresponding activation energies (Ea) for APC are determined using Arrhenius equation. The findings indicate that the Ea value of APC without any additives is 39.65 kJ/mol. Moderate amount addition of TMPTMA (0-1 phr) enhances the temperature sensitivity, however, silane incorporation alone significantly reduces Ea value by 7-12 kJ/mol. The Ea values are also utilized to estimate the compressive strength of APC, based on the equivalent time at the reference temperature (0 degrees C). The modified maturity method effectively predicts the compressive strength of APC cured under sub-zero temperatures. The estimated values closely match experimental data with errors controlled in +/- 10%. This work will provide basis and instruction on estimating strength and determining the safe timing for traffic opening when APC is used as a patch repair for roads and pavements.
Keywords: Acrylic polymer concrete; Arrhenius equation-based maturity method; Compressive strength; Sub-zero curing temperature